Increased image quality and reduced radiation dose and contrast media volume: a holistic approach to intracranial CTA. Issue 9 (September 2017) - Saade, C.; Al-Fout, G.; Mayat, A.; Brennan, P.C.; Hui, F.; Maroun, G.; Kikano, R.N.; Naffaa, L.
Abstract : Aim: To investigate the dose–length product (DLP) during intracranial computed tomography angiography (CTA) using a patient-specific contrast formula. Materials and methods: Intracranial CTA was performed on 120 patients using 64-channel CT. Patients were subjected in equal numbers to one of two acquisitions/contrast medium protocols. Protocol A, consisted of 80 ml contrast medium and protocol B, involved a novel contrast medium formula. In each protocol, contrast medium and saline were injected at a flow rate of 4.5 ml/s. The DLP and contrast volume (CV) were measured between each protocol and the data obtained were compared using two-tailed independent t -test. Results: Mean arterial vessel attenuation was up to 56% ( p< 0.01) higher using protocol B compared with A. In the venous system, the mean vessel attenuation was significantly lower in protocol B than A with a maximum reduction of 93% ( p< 0.001). The mean CV was significantly lower in protocol B (53±10 ml) compared to A (80±1 ml, p< 0.001). The scan time was equal in each protocol (B, 4.22±1.2 seconds; A, 4.01±1.3 seconds). A significant reduction in mean DLP was demonstrated in protocol B (3.99±0.22 mSv) compared to A (4.74±0.22 mSv; p =0.02). Conclusion: A significant reduction in CV and DLP during intracranial CTA can be achieved when employing a patient-specific contrast medium formula. Highlights: Patient-specific contrast media volume reduces venous contamination during intracranial CTA. Reduced contrast media volume results in reduction in delivered radiation dose. Increased reader confidence is associated with optimal image quality.